2021
DOI: 10.1080/16184742.2021.1903527
|View full text |Cite
|
Sign up to set email alerts
|

A bright spot for a small league: social media performance in a football league without a COVID-19 lockdown

Abstract: This document is the author's post-print version, incorporating any revisions agreed during the peer-review process. Some differences between the published version and this version may remain and you are advised to consult the published version if you wish to cite from it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 69 publications
(89 reference statements)
0
6
0
Order By: Relevance
“…Sport consumption and engagement has long been understood to occur not in isolation, but rather as part of a larger network of individuals forming a collective (Katz et al, 2019). Note the discontent voiced by fans, athletes and media pundits alike during the COVID-19 pandemic when most of the world's sporting competitions operated without crowds (Weimar et al, 2021).…”
Section: Collective Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…Sport consumption and engagement has long been understood to occur not in isolation, but rather as part of a larger network of individuals forming a collective (Katz et al, 2019). Note the discontent voiced by fans, athletes and media pundits alike during the COVID-19 pandemic when most of the world's sporting competitions operated without crowds (Weimar et al, 2021).…”
Section: Collective Engagementmentioning
confidence: 99%
“…This is particularly relevant in the sport context because the off-season periods and teams' seasonal ups and downs can play a role in how fans interact with the team and other actors in the ecosystem (e.g., Su et al, 2020). In this respect, good team performance tends to influence positive manifestations of non-transactional fan engagement (e.g., BIRGing;Trail et al, 2016), while a reduction in fan interaction with the team on social media is common during periods without on-field competition (Weimar et al, 2021).…”
Section: [Insert Table 3]mentioning
confidence: 99%
“…The authors' findings implied that social media enabled fans to perpetuate messages that elevate group distinctiveness, minimize in-group issues, and derogate out-group members. More recently, Weimar et al (2021) guided by social identity theory and using 3 months of social media data before, during, and 3 months after the COVID-19 lockdown, investigated whether fan interest toward smaller leagues suffered from the presence of bigger leagues. The study reported that interest in a league which remained active increased during COVID but went back to almost where it was previously after the revitalization of worldwide professional football leagues.…”
Section: Social Identity Theorymentioning
confidence: 99%
“…The NBA suspended play on March 11 after a player (Rudy Gobert) tested positive for COVID-19 several hours before he was due to play. As the pandemic ensued and games were not resumed, leagues and teams were forced to engage with fans using other content, media outlets, and social media outlets in particular (Hayes, 2022; Weimar et al, 2021).…”
Section: Social Media and The Covid-19 Pandemic-related Sport Disrupt...mentioning
confidence: 99%